PERSEPSI MASYARAKAT MENGENAI KINERJA APARATUR DESA DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI DESA TEMPOK KECAMATAN TOMPASO KABUPATEN MINAHASA - Sumilat, Sandria; Sampe, Stefanus; Lengkong, Johny P. (UNIVERSITAS SAM RATULANGI, 2024)
This research aims to determine community perceptions of the performance of village officials in administering village government. This research uses qualitative methods with a research focus on community perceptions regarding the performance of village officials in administering government in Tempok village, Tompaso subdistrict, Minahasa Regency. Community perceptions will be studied using the approach proposed by Anwar Prabu Mangkunegara, regarding performance indicators. According to him, to assess performance, you can use several indicators, namely: looking at the quality of work, quantity of work, accuracy and responsibility. From the research results, it is clear that the community's perception of the performance of village officials in Tempok village, seen from the indicators of work quality, work quantity, accuracy and responsibility, are all considered to be not good. This can be seen from the lack of understanding of village officials regarding their duties and functions. Apart from that, they are often not on duty at the right time, which affects the public service process. This is made worse by the unavailability of a village office as a place to carry out community services. Keywords: Perception; Performance; Village Apparatus